2016
DOI: 10.1038/srep38241
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates allergic inflammation by inhibiting key initiating factors in the initial stage of sensitization

Abstract: To illuminate the anti-allergy mechanism of astragaloside IV (AS-IV), we assessed its effects in a murine model of allergic contact dermatitis (ACD). AS-IV administered in the sensitization phase, rather than in the elicitation phase, dramatically alleviated the symptoms of allergic inflammation. We hypothesized that AS-IV exerts its anti-allergy effects by regulating the production of key pro-allergic cytokines based on the fact that interleukin (IL)-33 and thymic stromal lymphopoietin (TSLP) levels increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, TNF-α- and LPS-induced inflammatory reactions may be inhibited by AS-IV treatment via the NF-kB pathway in endothelial cells [8]. Evidence from pharmacological research and clinical practice suggests that AS-IV possesses effective anti-inflammatory properties and the ability to treat infectious diseases [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TNF-α- and LPS-induced inflammatory reactions may be inhibited by AS-IV treatment via the NF-kB pathway in endothelial cells [8]. Evidence from pharmacological research and clinical practice suggests that AS-IV possesses effective anti-inflammatory properties and the ability to treat infectious diseases [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the previous research 33) , donepezil was found to exert potent effects on inhibition of neuroinflammation and microglial activation. Lines of evidence have revealed that AS-IV is a bioactive compound with potent anti-inflammatory properties 13)- 15) , but the effect of AS-IV on neuroinflammation and related mechanism is not well elucidated. In LPS induced BV2 and primary microglia cells, AS-IV could significantly reduce the release of inflammatory mediators through activating NRF2/HO-1 via ERK signaling pathway 34) .…”
Section: Discussionmentioning
confidence: 99%
“…AS-IV has been shown to be effective in relieving allergic asthma [16,17]. As a representative bioactive compound of YPFS, we reported AS-IV ameliorated allergic inflammation in sensitization stage of AD by inhibiting TSLP and IL-33 production [14]. In this study, we firstly investigated the effect of AS-IV on anti-AD recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study elucidated that YPFS attenuated recurrent allergic inflammation of AD by repairing epithelial barrier defects in remission phase [13]. Furthermore, by means of bioactive components screening, we found AS-IV as a potent bioactive component of YPFS, could ameliorate the allergic inflammation by inhibiting alarmin cytokines such as thymic stromal lymphopoietin (TSLP) and IL-33 in sensitization stage of AD [14]. However, whether AS-IV could also effectively alleviate the recurrent allergic inflammation of AD was still unknown.…”
mentioning
confidence: 98%